Implementasi edukasi pencegahan anemia pada remaja putri di SMPN B Srikaton - Indah Dewi Ridawati; Wella Juartika; Jhon Feri; zuraidah (Nur Science Institute, 2026)
Low knowledge about anemia and its prevention is a risk factor for anemia in school-age children. Based on initial observations at SMPN B Srikaton, most adolescent girls do not yet have an optimal understanding of anemia prevention and early detection. This community service activity aims to increase adolescent girls’ knowledge of anemia prevention and detection through educational leaflets. The activity was carried out on Friday, February 14, 2025, involving 30 adolescent girls and 2 female teachers, in the form of health education delivered through materials and leaflet distribution. It followed the preparation, implementation, and evaluation stages. The evaluation was conducted using a pre-test and a post-test. The results showed that the average knowledge score increased from 65 in the pre-test to 83 in the post-test. Leaflets have proven effective for adolescent health education because they have a simple format, are easy to understand, and can be reread by participants after the educational activity. Delivering information through leaflets with pictures and brief explanations helps improve adolescents’ understanding of the provided health material. Continuous education needs to be carried out.